Consumer contracts in Colombia - Rico Charry, Hermes Fernando (DIXI, 2019)
Objective: The general objective of this article is to carry out an analysis of contracts in general, and consumer contracts in particular, through a proactive investigation based on a dogmatic methodology and a doctrinal, jurisprudential and legislative analysis. Methodology: Based on the proposed analysis, the study of different concepts and positions on contracts and their background elements will be presented: the offer, acceptance and improvement of the contract; the consumer contract will then be addressed, its characteristics as an asymmetric contract and its relationship with the adhesion contract, ending with a conceptualization of the consumer contract as a standard contract. Conclusions: The completion of the contract requires compliance with the conditions of the undertaking and with the formalities established by law for each contract case. Consumer contracts are asymmetric, because where consumers are concerned, economic power and information are held by the producers or merchants. In turn, the consumer contract is a regulated contract, with a special level of protection because there is no equality between the contracting parties. This protection is insufficient, given the dynamics of the forms of offering and buying consumer goods, which evolves to the point that the legislation in this regard, generally, is behind schedule, generating an imbalance between producers or marketers and consumers.